Substantial supervision performed in prophylactic care of children and adolescents by nurses and midwives in Silesia Region - Smektała, Barbara; Lenkiewicz, Lech; Stasiak, Iwona; Kollbek, Piotr (Polish Journal of Public Health, 2009)
Nurses and midwives take prophylactic care of people who are 0-19 years old. From the birth to the end of 2nd month of life the child is being cared for at home by a midwife, then, until it is 1 year old – by a family/community nurse. Further prophylactic medical care is being discontinued until the 6th year of life, when the care of children is being taken over by school nurses or hygiene specialists.In the years 2005-2007 Lower Silesia Centre for Public Health controlled 695 nurses and midwives working in the family environment as well as nurses and hygiene specialists working at medical prophylaxis and fi rst aid rooms or some other institutions offering services in the fi eld of medical prophylactic care of children and schoolchildren.Many repeatedly occurring improper actions were tracked down this way.The most important mistakes were: unsatisfactory cooperation between various institutions caring of children, the lack of medical prophylaxis and fi rst aid rooms in some schools, faulty medical fi les, the lack of dentist care, improper environmental care, short staffi ng of nurses and midwives in comparison with actual needs and their resulting overload with children they take care of.